Playing like champions: Notation analysis of European and South American international football - Lee, D.; Shelton, T.; Reilly, T.; Rienzi, E. (Journal of Sports Sciences, 1999)
Es wird die Spielweise der Fußballmannschaften von Uruguay und Deutschland bei je 4 internationalen Spielen verglichen (1995 Copa America in Uruguay und Europameisterschaft 1996).